Enhancing the efficacy of Burkholderia cepacia B23 with calcium chloride and chitosan to control anthracnose of papaya during storage - Rahman, M. A.; Tengku Muda Mohamed, Mahmud; Kadir, Jugah; Abdul Rahman, Russly; Begum, M. M. (Asian Network for Scientific Information, 2009)
The efficacy of the combination of Burkholderia cepacia B23 with 0.75% chitosan and 3% calcium chloride (CaCl2) as a biocontrol treatment of anthracnose disease of papaya caused by Colletotrichum gloeosporioides, was evaluated during storage. The growth of B. cepacia B23 in papaya wounds and on fruit surfaces was not affected in presence of chitosan and CaCl2 or combination throughout the storage period. The combination of B. cepacia B23 with chitosan-CaCl2 was more effective in controlling the disease than either B. cepacia B23 or chitosan or other combination treatments both in inoculated and naturally infected fruits. Combining B. cepacia B23 with chitosan-CaCl2 gave the complete control of anthracnose infection in artificially inoculated fruits stored at 14 oC and 95% RH for 18 days, which was similar to that obtained with fungicide benocide¢ç. Moreover, this combination offered a greater control by reducing 99% disease severity in naturally infected fruits at the end of 14 days storage at 14 oC and 95% RH and six days post ripening at 28¡¾2oC, which was superior to that found with benocide¢ç or other treatments tested. Thus, postharvest application of B. cepacia B23 with chitosan-CaCl2 as enhancers represents a promising alternative to synthetic fungicides for the control of anthracnose in papaya during storage.